A notched UWB microstrip patch antenna for 5G lower and FSS bands. Issue 4 (14th February 2022) - Mahfuz, M.M. Hasan; Islam, Md Rafiqul; Habaebi, Mohamed Hadi; Sakib, Nazmus; Hossain, A. K. M. Zakir
Abstract: In ASEAN countries, the fifth generation (5G) forum proposed a 5G application lower frequency band (4.5–5.5) GHz and the fixed satellite service (FSS) C‐band at (3.3–4.2) GHz. Previous research works have demonstrated that the complexity of antenna design, large size and in most of the cases, active elements that were added to antenna has made the antenna costly. Therefore, this research work focused on developing a single band notched (SBN) and double band notched (DBN) antennas by creating notched bands for 5G lower band from 4.5 to 5.5 GHz and C‐band 3.3 to 4.2 GHz applications in antenna UWB spectrum. An UWB antenna has been developed using low‐cost FR‐4 substrate with partial grounding (PG) on a rectangular patch. A single band and dual band notched UWB antennas were realized for the 5G lower band through the use of a slot at the top of the radiating patch and by adding an arc shape open loop (ASOL) on the UWB antenna. Both antennas are fabricated using the same FR‐4 substrate and tested using Vector Network Analyzer (VNA). The voltage standing wave ratio (VSWR), return loss, gain, and 2‐D radiation pattern of the test results prove that all antennas have excellent performance (compared to previous research works) in notched band and UWB band frequencies. Therefore, developed single notch and dual notch UWB antennas are proposed as good candidates for 5G lower band and C‐band notched application environment.